Aktivitas Trombolitik Fraksi Protein 27 KDA Kelenjar Saliva Aedes Aegypti - Silfia Ayuni (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2026)
Thrombosis is a major cause of various cardiovascular diseases, so the development of alternative thrombolytic and antithrombotic agents is needed. The salivary glands of Aedes aegypti are known to contain various bioactive proteins that have the potential to affect the hemostasis process, one of which is a protein with a molecular weight of 27 kDa, also known as aegyptin. This study aims to analyze the activity of the 27 kDa protein fraction from the salivary glands of Ae. aegypti, which has the potential as a new thrombolytic agent. The 27 kDa protein fraction was obtained through salivary gland extraction, fraction separation based on molecular weight using SDS-PAGE, and purification by electroelution and dialysis. The results of the purification of 150 protein bands from the 27 kDa fraction showed a concentration of 1.5 mg/ml. Proteolytic activity was tested using Skim Milk Agar (SMA) media with the well method and the direct drop method. The results of the proteolytic activity test showed that the 27 kDa protein fraction did not show proteolytic activity up to 72 hours of incubation in both methods. This indicates that the proteolytic activity of the 27 kDa protein fraction was not detected under the assay conditions used. Therefore, further studies using more specific methods are needed to confirm the biological activity of the 27 kDa protein fraction.
:: Finalisasi file repositori 20 Juli 2026_Kurnadi
Keywords: Aedes aegypti; trombolytic; proteolytic activity; 27 kDa protein fraction